1998
DOI: 10.1302/0301-620x.80b4.8651
|View full text |Cite
|
Sign up to set email alerts
|

The 'dropping' and 'hornblower's' signs in evaluation of rotator-cuff tears

Abstract: We studied 54 patients operated on for combined supraspinatus and infraspinatus rotator-cuff tears. The presence or absence of the dropping and hornblower's clinical signs of impaired external rotation were correlated with Goutallier stage-3 or stage-4 fatty degeneration of infraspinatus and teres minor. These grades of fatty degeneration have previously been correlated with a poorer outcome from reconstructive surgery. We found that hornblower's sign had 100% sensitivity and 93% specificity for irreparable de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(67 citation statements)
references
References 3 publications
3
60
0
4
Order By: Relevance
“…We agree with Tokish et al who found the subscapular muscle and tendon can be well tested with the press belly test [28] and with Walch et al who stated the teres minor muscle and tendon can be well evaluated with the hornblower' sign [21]. Our study also confirms the statement of Hertel et al who found clinical testing for lag signs to be efficient, reproducible, and reliable in evaluating the teres minor tendon and muscle [8].…”
Section: Discussionsupporting
confidence: 91%
“…We agree with Tokish et al who found the subscapular muscle and tendon can be well tested with the press belly test [28] and with Walch et al who stated the teres minor muscle and tendon can be well evaluated with the hornblower' sign [21]. Our study also confirms the statement of Hertel et al who found clinical testing for lag signs to be efficient, reproducible, and reliable in evaluating the teres minor tendon and muscle [8].…”
Section: Discussionsupporting
confidence: 91%
“…Accuracy of the empty can test (sensitivity 86%), drop arm sign and external rotation lag signs (specificity 90–97%) was similar in this study compared with previous reports for rotator cuff integrity [16–18, 63, 64]. However, clinical tests previously reported to be diagnostic for subacromial “impingement” pathology including Hawkins-Kennedy test and painful arc in abduction [34] were of limited value for identifying SAP in the current study.…”
Section: Discussionsupporting
confidence: 83%
“…A positive external rotation lag sign and a positive hornblower’s sign are indicative of posterior cuff deficits and external rotation inability [72, 73]. Moreover a positive hornblower’s sign has been associated with irreparable teres minor tears [73] and advanced fatty infiltration [7, 14] and is related to poor outcomes in tendon transfers [74]. This has been highlighted in the studies of Gerber et al .…”
Section: Indications-contraindication For Ld Transfermentioning
confidence: 99%
“…Reverse shoulder arthroplasty has been used with success in treating cuff tear arthropathies and restore active elevation [34-37]; it does not however restore active external rotation and may lead to reduced functional results [34, 123, 124]. Pseudoparalysis of external rotation has been mainly attributed to deficiency of the teres minor [72, 73, 125], relative to chronicity with ensuing atrophy or fatty infiltration [7, 126]. In this context, extending indications of LD tendon transfer to be performed in conjunction with reverse shoulder arthroplasty has provided a solution; as it has been demonstrated to increase external rotation and provide a better control of the arm in space [38-40].…”
Section: Reverse Shoulder Arthroplasty and Ld Transfermentioning
confidence: 99%